Multilayer Density Analysis of Cellulose Thin Films - Sampl, Carina; Niegelhell, Katrin; Reishofer, David; Resel, Roland; Spirk, Stefan; Hirn, Ulrich (Frontiers in Chemistry, 2019)
An approach for the multilayer analysis of polysaccharide thin films at the example of cellulose is presented. In detail, a multilayer model was developed for the evaluation of the films, wherein the cellulose film was split into a so called ‘roughness layer’ present at the surface and a ‘bulk layer’ attached to the surface. For this approach, a combination of multi-parameter surface plasmon resonance spectroscopy and atomic force microscopy (AFM) was employed to detect changes in the properties of the surface near layer and the bulk layer. The surface region of the films featured a much lower density than the bulk. Further, these results have been validated by X-ray reflectivity studies, indicating a similar layered structure with reduced density at the surface near regions. Finally, limitations and challenges of the multilayer model evaluation method of cellulose thin films were discussed.